2015
DOI: 10.2147/opth.s79948
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone intravitreal implant in the treatment of diabetic macular edema

Abstract: Diabetic macular edema (DME) resembles a chronic, low-grade inflammatory reaction, and is characterized by blood–retinal barrier (BRB) breakdown and retinal capillary leakage. Corticosteroids are of therapeutic benefit because of their anti-inflammatory, antiangiogenic, and BRB-stabilizing properties. Delivery modes include periocular and intravitreal (via pars plana) injection. To offset the short intravitreal half-life of corticosteroid solutions (~3 hours) and the need for frequent intravitreal injections, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 88 publications
0
96
0
1
Order By: Relevance
“…However, clinical utility of DEX has been limited by a short half-life of approximately 3 h. To overcome this drawback, a biodegradable DEX drug delivery system was developed [15]. There have been several studies which showed the efficacy of DEX implant using DEX delivery system in refractory DME [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…However, clinical utility of DEX has been limited by a short half-life of approximately 3 h. To overcome this drawback, a biodegradable DEX drug delivery system was developed [15]. There have been several studies which showed the efficacy of DEX implant using DEX delivery system in refractory DME [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…The dexamethasone intravitreal implant 0.7 mg (DEX implant, Ozurdex®, Allergan Inc., Irvine, CA, USA), a long-acting sustained-release corticosteroid [13], has been shown to be effective in treating DME [14-17]. Upon treatment with DEX implant, pro-permeability factors were reduced in aqueous samples [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies and case series have reported outcomes either following a single DEX implant [14, 17, 19, 20] or retreatment with DEX implant after 6 months [15, 16]. One small retrospective analysis reported the use of repeated as-needed DEX implants [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although most recent reports question the effectiveness of triamcynolon treatmnet, anecortave acetate and dexametazone are still applied [64,65].…”
Section: Treatment Of Diabetic Retinopathymentioning
confidence: 99%